2023
DOI: 10.1073/pnas.2215237120
|View full text |Cite
|
Sign up to set email alerts
|

A conserved zinc-binding site in Acinetobacter baumannii PBP2 required for elongasome-directed bacterial cell shape

Abstract: Acinetobacter baumannii is a gram-negative bacterial pathogen that causes challenging nosocomial infections. β-lactam targeting of penicillin-binding protein (PBP)–mediated cell wall peptidoglycan (PG) formation is a well-established antimicrobial strategy. Exposure to carbapenems or zinc (Zn)-deprived growth conditions leads to a rod-to-sphere morphological transition in A. baumannii , an effect resembling that caused by deficiency in the RodA–PBP2 PG synthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 80 publications
1
3
0
Order By: Relevance
“…Our analysis thus far suggested that strains lacking 2903 or lpsB —two mutants proposed to be involved in KdoIII residue addition to the core oligosaccharide—exhibited defects in cell division to varying extents. Cell division errors much like those observed here are often found in cells with underlying defects in peptidoglycan cell wall synthesis ( 35 37 ). It was unclear why this might be the case as there is no known overlap between core oligosaccharide synthesis and cell wall synthesis.…”
Section: Resultssupporting
confidence: 65%
“…Our analysis thus far suggested that strains lacking 2903 or lpsB —two mutants proposed to be involved in KdoIII residue addition to the core oligosaccharide—exhibited defects in cell division to varying extents. Cell division errors much like those observed here are often found in cells with underlying defects in peptidoglycan cell wall synthesis ( 35 37 ). It was unclear why this might be the case as there is no known overlap between core oligosaccharide synthesis and cell wall synthesis.…”
Section: Resultssupporting
confidence: 65%
“…In addition to validating the two genes, Pal and MreB, which influence rod-shaped bacterial morphology in this study, other genes known to affect bacterial morphology, such as RodZ and PBP [47,48], were not directly obtained. One possible reason is that the shapes obtained from online sources or through book references and extrapolation may still contain errors.…”
Section: Key Genes Regulating Bacterial Rod Shapementioning
confidence: 95%
“…Whereas many β-lactamases are plasmid-borne and exhibit few variations among different bacteria, the peptidoglycan transpeptidases from each bacterial species may have unique features. Most recently, two groups reported the identification of highly conserved zinc-binding domains in C. difficile and A. baumannii PBP2, which in C. difficile was found to be an essential transpeptidase for cell growth [165,170]. This motif in PBP has never been observed in any other known PBP structures, but sequence analysis has suggested its prevalence in many bacteria, particularly the Firmicutes [165].…”
Section: Understanding the Transpeptidase Targetsmentioning
confidence: 99%